(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The human body is an incredible piece of engineering. The future of childbirth, which mayinclude things like test-tube infants and surrogate mothers thanks to advances in reproductive andcloning technologies, will usher in possibilities in the sexual realm that were previously unimaginable. Awoman who consents to get pregnant for the purpose of carrying and delivering a child for anothercouple or individual to raise is said to engage in the practise of surrogacy, which is a kind of assistedreproduction. It is possible that the intended parents will be acknowledged as the child’s legal parentsfrom the moment of birth in those countries that have legalised the practise of surrogacy. In India, thepractise of commercial surrogacy, sometimes known as Womb for hire, is a burgeoning industry. Therise of reproductive tourism is a phenomena that emerged relatively recently in our globe, which is in theprocess of quickly globalising. Poor women in countries like India, which already have an extremely highincidence of maternal mortality, are being exploited by the surrogacy industry. In the context ofsurrogacy, this study discusses concerns pertaining to paternity as well as the right of women to health.It is imperative that the government of India give serious consideration to passing a legislation toregulate surrogacy in India so that couples who choose to pursue this option can be protected andguided. Patients would always be misled, and the surrogates will be exploited, in the absence of a legalstructure that is unassailable.